Death of a laken ; Better than nothing ; The Perfect alternative [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1993)
A deadly pollutant killed over a million pesos worth of fish in Laguna de Bay. The multigrade system of education brings together first second and third grader under one classroom. Tackles one of the fastest singing band in Manila.
Death of a lake (15 min.) -- Better than nothing (18 min.) -- The Perfect alternative (17 min.)
VHS.
Keywords: Perfect (Singing group); Fishes -- Effect of chemicals on -- Philippines; Factory and trade waste -- Philippines -- Laguna; Education, Rural -- Environmental aspects. -- Philippines; Alternative rock music -- Philippines; Band musicians -- Philippines